EXAMINING OF INFORMATION LITERACY AND SCIENCE PROCESS SKILLS TOWARDS GRADE POINT AVERAGE: A PRELIMINARY RESEARCH - Hasan Subekti; Mohammad Taufiq; Ibrohim Ibrohim; Hadi Suwono; Herawati Susilo (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
Information Literacy (IL) and Science Process Skills (SPS) have been widely examined to enhance the quality of learning, especially in higher education, in which information technology has become the basis of human life. This research aims to explore the relationship between IL and SPS to the grade point average (GPA) of pre-service science student. Determination of samples using a typical case sampling is 278 students from 329 active students in the program at S1-Science Education, Surabaya State University (UNESA). This research uses quantitative approaches. The source of data is a test result of IL and SPS towards a GPA in the odd 2017/2018 semester. The data were analyzed using the Minitab 16 program. The results of the data analysis showed that = 26,69 ˃ 3,03 = = (0,05;2;275) or in other words support data to reject with confidence level 95%. This investigation concludes that there is a significant relationship between variable information literacy and science process skills together against the grade point average. The results of the research are expected to be one of the considerations in choosing and determining the right learning of science teachers,